Homogeneous myxoid liposarcomas mimicking cysts on MRI: A challenging diagnosis. Issue 102 (May 2018) - Crombé, A.; Loarer, F. Le; Alberti, N.; Buy, X.; Stoeckle, E.; Cousin, S.; Toulmonde, M.; Coindre, J.M.; Italiano, A.; Kind, M.
Abstract: Objectives: Myxoid liposarcoma (M-LPS) is the second most frequent subtype of liposarcoma. Foci of fat on MRI are strongly suggestive of this diagnosis. The aims of this study are to (i) assess the prevalence of perfectly homogeneous M-LPS-mimicking cyst and characterize their associated clinical and pathological features and to (ii) identify helpful clues to prevent misdiagnosis when encountered with a cyst-like lesion in soft tissue parts. Methods: MR images from 32 consecutive pathologically proven M-LPS and round cell liposarcomas (RC-LPS) were retrospectively reviewed independently by two radiologists at our institution. Location, morphology, signals, lesion architecture, heterogeneity, margins and periphery were systematically assessed in each case. Medical records were checked for initial and definitive histopathological diagnosis, therapeutic managements and outcomes. Histopathological specimens of cyst-like M-LPS were reviewed for the study. Results: We have identified seven perfectly homogeneous well-defined cyst mimickers (21.9%) located on the limbs, all but one being deep-seated. These tumors were significantly smaller than the conventional M-LPS (p = 0.0005). Six lesions were initially diagnosed as benign; 4 patients underwent marginal surgical resection without prior diagnosis and 2 cases were put under medical surveillance, one of which progressed towards classical RC-LPS on follow-up MRI. No specific pathological features could be identified nor were any clinical adverse outcomes recorded. Conclusion: "Cyst" on MRI, without pathological adjacent joint, necessitates ultrasonography with Doppler and intravenous Gadolinium agent injections as subsets of M-LPS can mimic cyst on MRI. Cyst-like M-LPS, due to their smaller size and relative favorable outcome, could have better prognosis.